TATA KELOLA USAHA MIKRO DAN KECIL (UMK) BERBASIS HUKUM DAN EKONOMI (PENDEKATAN PENGABDIAN MASYARAKAT UNTUK PEMBERDAYAAN EKONOMI LOKAL) - Fatma Ayu Jati Putri; Insan Pribadi; Erna Wati; Erlina Sih Rahayu; Muflik Malikun (LP2M STP Mataram, 2024)
This paper addresses the significance of the governance of micro and small enterprises (SMEs) based on legal and economic foundations as a crucial framework for their sustainability and growth. With effective governance, SMEs can operate efficiently, transparently, and sustainably. The community engagement approach plays a central role in realizing effective SME governance through collaboration among academics, practitioners, government entities, and local communities. The primary goal is the empowerment of local economies, with community engagement approaches supporting the growth and success of SMEs, indirectly advancing local economies, and enhancing the well-being of local communities. The conclusion emphasizes that collaboration and synergy among stakeholders are key elements in achieving these objectives